1985
DOI: 10.1111/j.1432-1033.1985.tb09170.x
|View full text |Cite
|
Sign up to set email alerts
|

The accessibility of 5-methylcytosine to specific antibodies in double-stranded DNA of Xanthomonas phage XP12

Abstract: Antibodies specifically directed to 5-methylcytidine were raised in rabbits and purified by affinity chromatography. The accessibility of 5-methyldeoxycytidine (m'dcyd) to such antibodies was studied with DNAs from various origins. The reaction was followed by measuring the retention of radiolabelled DNA by antibodies on nitrocellulose filters, by immunoprecipitation, by gel filtration and was visualized with the electron microscope. Antibodies did not bind to Escherichiu coli B DNA, which is deficient in m'dC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Moreover, global changes of certain epigenetic modifications may have their independent diagnostic value, especially when analyzed in correlation with other phenotypic markers, an opportunity offered by up-to-date laser scanning microscopic systems (20,21). Development of antibodies and chimeric methyl CpG-binding antibody-like proteins (24)(25)(26)(27), both recognizing CpG with high specificity, has opened novel perspectives for the diagnostic analysis of global methylation states. Anti-5mC antibodies are commercially available through various sources (e.g., Abcam and Biocarta US).…”
Section: Testing Global Epigenetic Changes By Laser Scanning Microscomentioning
confidence: 99%
“…Moreover, global changes of certain epigenetic modifications may have their independent diagnostic value, especially when analyzed in correlation with other phenotypic markers, an opportunity offered by up-to-date laser scanning microscopic systems (20,21). Development of antibodies and chimeric methyl CpG-binding antibody-like proteins (24)(25)(26)(27), both recognizing CpG with high specificity, has opened novel perspectives for the diagnostic analysis of global methylation states. Anti-5mC antibodies are commercially available through various sources (e.g., Abcam and Biocarta US).…”
Section: Testing Global Epigenetic Changes By Laser Scanning Microscomentioning
confidence: 99%
“…Other alternative methods include the wide range of immunological DNA methylation assays that suddenly appeared after it was first found that methylcytosine was accessible to specific antibodies in 1985 (Adouard et al, 1985). This vital development paved the way for the possibility to chart the DNA methylation landscape on a cell to cell basis.…”
Section: Early Non-specific Methodsmentioning
confidence: 99%
“…In the early 1980s, antibodies were raised that could specifically target and bind 5mC on genomic DNA. There were also other variations of this immunological method, with one alternative method utilizing radiolabeling of DNA, followed by 5mC pull-down with rabbit polyclonal antibodies and subsequently measuring radioactivity of the enriched DNA to determine overall levels of 5mC [21]. In the proposed method, genomic DNA is extracted and immobilized to nitrocellulose paper.…”
Section: Measuring Genomic Levels Of 5-methylcytosine and 5-hydroxymementioning
confidence: 99%